KONSEP MAWAS DIRI SURYOMENTARAM DENGAN REGULASI EMOSI - Pratisti, Wiwien Dinar; Prihartanti, Nanik (Universitas Muhammadiyah Surakarta, 2012)
Multidisciplinary study is often conducted to investigate emotions. Research on emotions focuses on the situation, behavior and beliefs that underlie the emergence of emotion, and not on the emotion itself. Research on emotion not only examine the types of emotions alone but is associated with the situation, behaviors, and beliefs. It is inseparable from emotion regulation system that is owned by someone. Gross & Thompson and Kalat & Shiota state that emotion regulation may serve as a coping strategy to face psychological distress. Prihartanti?s research shows that in Javanese culture (Suryomentaram concept), a healthy person must be a able to adapt to the environment with introspective methods. Theoretically, the introspective method is similar to the concept of emotion regulation version of western culture. Therefore, this study intends to study the difference between the two concepts.The research method used is a comparative study using two approaches, namely qualitative and quantitative. A qualitative approach was conducted in the first year with the aim of acquiring data directly from the field then compiled into a gauge or scale. Quantitative approaches were used to examine differences between the introspective emotion regulation. Result shows that there are differences and similarities between the concepts of introspection in Suryomentaram with emotion regulation. The similarity lies on the ultimate goal, role and function, cognitive approaches and generalizations, while the difference lies in the step or process.